A process-oriented system for mobile dispatcher-driver communication of road haulage contractors. (30th March 2005) - Erkens, Elmar
Within the transportation business, we can observe a tendency towards the integration of the ongoing delivery process within in-house processes. The idea is to strike for the goal of laying the foundation for dynamic vehicle planning as well as vehicle control. In order to achieve this it will be necessary to improve on the often cost-intensive, time-consuming and error-prone mobile communications between dispatchers and drivers typical for medium-sized German transport operators. The following paper describes a communication system for vehicle-fleet control that supports the working processes of the driver as well as the forwarding agent. We have succeeded in substituting the prevalent mobile vocal communication with a continuous databased communication. Both parties are now enabled to obtain online access to all necessary and updated information needed for their individual sequence of operation at any time.